Does Violence Always Win?: Learning From René Girard (1923-2015) - Reineke, Martha J. (Religion dispatches, 2015)
Last August, a photo of a grieving father holding a child who had not survived the dangerous passage from Syria to Europe elicited widespread compassion from Americans. But following the Paris attacks on November 13, 2015, Governor Chris Christie and Dr. Ben Carson, Republican candidates for preside